First serine protease inhibitor isolated from Rhinella schneideri poison - Shibao,Priscila Y T (2015)
Background Toad secretions are a source of molecules with potential biotechnological application on a wide spectrum of diseases. Toads from theRhinella family have two kinds of poisonous glands, namely granular and mucous glands. Rhinella schneideritoads produce granular secretions that comprise a great number of molecules, including serine proteases inhibitors. Serine proteases, such as trypsin, chymotrypsin and elastase, are enzymes that have a serine amino acid into its catalytic site and can be found in a large number of vertebrate species and pathogenic microorganisms. Therefore, the present work aims to purify a serine protease inhibitor from Rhinella schneiderigranular secretions.Findings This study presents the protocol used to purify a serine protease inhibitor from the Rhinella schneideri poison. The granular secretion was submitted to dialysis in order to separate the low molecular weight compounds, which were submitted to a reversed phase-fast protein liquid chromatography fractionation step in a C2C18 column. The major fractions were tested over trypsin, chymotrypsin and elastase through colorimetric assay. The inhibition tests were performed with the enzyme in absence (positive control) and presence of fractions, denatured enzyme (negative control) and the respective chromogenic substrate. Rs20 was the compound with the major inhibitory activity over chymotrypsin, inducing a delay in the formation of the chromogenic enzymatic product. The structure characterization of Rs20 was performed by high resolution electronspray ionization-mass spectrometry (HRESI-MS) and gas chromatography coupled with mass spectrometry (GC-MS). HRESI showed an intense signal suggesting the presence of bufadienolide with less than 10 ppm error. In addition, it was observed a low intense signal at m/z399 that could be lithocholic acid, a biosynthetic precursor of bufadienolide. Finally, GC-MS analysis applying NIST library identification reinforced this hypothesis.Conclusions The current study have isolated and partially characterized the function and structure of the first bufadienolide with inhibitory action over chymotrypsin.